2020
DOI: 10.1177/1524838020933865
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Emerging Adults After Adverse Childhood Experiences: A Qualitative Systematic Review

Abstract: Introduction: Even as children experience adversity, they can become resilient adults, in large part due to their social supports as emerging adults. Objective: Authors examine constructs of social support applied to the concept of resilience among emerging adults having experienced adverse childhood experiences (ACE). Method: Authors conducted a meta-ethnography with six databases between January 1998 and October 2019. Inclusion criteria were as follows: (i) original peer-reviewed qualitative or mixed-method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 57 publications
7
29
0
Order By: Relevance
“…Resilience is also culturally and contextually constructed (Ungar, 2004(Ungar, , 2008Ungar & Liebenberg, 2011). Indicators of resilience are influenced by cultural beliefs (e.g., Confucian beliefs on tolerance of adversity), familial structure (e.g., conforming to authority) and social norms (e.g., filial piety) (Leung et al, 2020). For example, Ho, Chan, Shevlin, et al (2019) found that the ability to endure and conform during hardships may be perceived as a culturally appropriate indicator of resilience among Chinese young adults, in contrast to the value placed on resisting convention among Western youth.…”
Section: Measuring Aces and Resilience In Chinese Culturementioning
confidence: 99%
“…Resilience is also culturally and contextually constructed (Ungar, 2004(Ungar, , 2008Ungar & Liebenberg, 2011). Indicators of resilience are influenced by cultural beliefs (e.g., Confucian beliefs on tolerance of adversity), familial structure (e.g., conforming to authority) and social norms (e.g., filial piety) (Leung et al, 2020). For example, Ho, Chan, Shevlin, et al (2019) found that the ability to endure and conform during hardships may be perceived as a culturally appropriate indicator of resilience among Chinese young adults, in contrast to the value placed on resisting convention among Western youth.…”
Section: Measuring Aces and Resilience In Chinese Culturementioning
confidence: 99%
“…The path from childhood adversities to later health problems is not inevitable, and children can become resilient adults, for example through available social support as emerging adults [ 22 , 23 ]. For this reason, one helpful approach may be to use a paradigm with enhanced weight on resilience and ways of coping with an adverse experience.…”
Section: Introductionmentioning
confidence: 99%
“…Although research on resilience in the period of emerging adulthood has accelerated more recently, many questions remain (Leung, Chan, & Ho, 2020;O'Connor et al, 2016).…”
Section: Predictions From Parenting and Personality In Adolescencementioning
confidence: 99%